Serum Concentrations of Trace Elements in Patients with Ulcerative Colitis - Hamidreza Joshaghani; Taghi Amiriani; Reza Goodarzi; Honeyeh-sadat Mirkarimi; Sima Besharat; Gholamreza Roshandel; Bahar Kolasangiani; Samaneh Sadat Aghili (Golestan University Of Medical Sciences, 2018)
Introduction: Nutritional status of patients with inflammatory bowel disease is estimated to be lower than optimal. This study was designed to compare the serum level of some trace elements in patients with ulcerative colitis (UC). Materials and methods: This cross-sectional study was performed in 2015-2016, on 60 recently diagnosed UC patients (30 with active UC and 30 with inactive UC) who were recruited from registry of the Golestan Research Center of Gastroenterology and Hepatology (Gorgan, Iran) through simple random sampling. Thirty healthy individuals were also recruited as controls. Demographic data and disease activity index were recorded through a checklist. Serum levels of copper (Cu), zinc (Zn), selenium (Se) and magnesium (Mg) were measured by atomic absorption spectroscopy. Data were analyzed using SPSS 16 at significance level of 0.05. Results: Mean serum level of Cu in the patients (0.75±0.25 mg/L) was significantly lower than in the controls (1.11±0.3 mg/L) (P=0001). Similarly, mean serum level of Mg in the patients (15.84±4.3 mg/L) was significantly lower than in the controls (19.48±15.7 mg/L) (P=0.001). Mean serum level of Se was slightly higher among the UC patients, while mean serum level of Zn was slightly lower in the UC patients compared with the controls. Conclusions: Our results show that UC patients have significantly lower Cu and Mg levels compared to healthy individuals. However, serum Zn and Se levels do not differ significantly between the UC patients and the control individuals. Further studies are required to confirm the results of this study.